Anfractuous assemblies of IMP dehydrogenase and CTP synthase: new twists on regulation?. (4th October 2018) - McCluskey, Gregory D.; Bearne, Stephen L.
Abstract : CTP synthase (CTPS) and IMP dehydrogenase (IMPDH) catalyse the rate‐limiting steps of de novo CTP and guanosine nucleotide biosynthesis, respectively, and form filament assemblies in response to inhibitors. A recent study explores the morphology and dynamics of these assemblies using fluorescence and super‐resolution confocal microscopy with cell lines expressing CTPS1 and IMPDH2 fusion proteins. The formation and dismantling of mixed assemblies depends on nucleotide levels, suggesting a co‐regulation function.